The implementation of role play in supporting speaking class - Anjani, Elisa Putri; Yuliati, Yuliati (ELT Forum: Journal of English Language Teaching, 2025)
In the context of 21st-century education and the growing importance of communicative competence, oral instruction in English as a foreign language (EFL) classrooms faces increasing expectations and ongoing challenges. The current Indonesian high school classroom, marked by the “Kurikulum Merdeka”, requires instructional strategies that promote student engagement, collaboration, and meaningful oral communication. This paper discusses how role play can be integrated into English teaching at the senior high school level in Indonesia to strengthen students’ oral communication skills. Based on the principles of communicative language teaching, sociocultural theory, and cooperative learning, role-play is viewed not only as a teaching activity but also as a strategic framework for language development. This article synthesizes relevant theoretical and empirical literature highlights the transformative potential of role-play, and proposes a practical framework for its implementation in Indonesian classrooms. Considering challenges such as teacher preparation, class size, and assessment focus, and then propose strategic considerations to address these challenges. By repositioning role-play as a reflective, student-centered process rather than a performance-oriented task, this article advocates for its inclusion as a core component of oral instruction. Role-play not only promotes language development but also enables EFL learners to build confidence, empathy, and autonomy, which are essential for developing 21st-century communication competence.